The Influence of Using Microsoft Office SWAY Based Learning Media on Student’s Learning Outcomes in Educational Foundations Courses at Universitas Muhammadiyah Palembang - Lestari, Winda (Journal of Social Work and Science Education, 2024)
This study aims to find out is there an influence of using Microsoft Office SWAY-based learning media on student’s learning outcomes in the Foundations of Education course at Universitas Muhammadiyah Palembang? This study uses a quantitative which is used to research certain populations and samples, with the aim of testing predetermined hypotheses. In this study, the respondent was all students of the first semester education administration study program in the Foundations of Education course, totaling 30 students. The results showed that there is an influence of the use of Microsoft Office SWAY-based learning media on student learning outcomes in the Foundations of Education course at the Universitas Muhammadiyah Palembang.